2015
DOI: 10.1136/bmjsem-2015-000014
|View full text |Cite
|
Sign up to set email alerts
|

Athletes with higher VO2max present reduced oxLDL after a marathon race

Abstract: BackgroundDuring a session of prolonged and exhaustive exercise, such as a marathon race, large quantities of free radicals are produced and can oxidise (ox) several molecules, such as low-density lipoprotein (LDL). To prevent oxidative damage, athletes present higher antioxidant levels. However, the effect of marathon running on the natural IgM or IgG anti-oxLDL autoantibodies is not understood. Thus, we investigated the effect of a marathon race on oxidative stress and the mechanisms of control of this stres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…So, the BMI values found in the TRAINED group and also the negative correlation found in our study between LOOH and the oxLDL levels reinforce the consistence of the favorable effects of the combined aerobic-resistance exercise training on the redox indexes. Moreover, we also found that in the TRAINED group, TAC levels were higher than in the SED group, which could buffer oxidative stress, thereby preventing the LDL oxidation [32]. Previous studies have also shown beneficial actions of exercise training protocols, including combined aerobic-resistance exercise training on the antioxidant defenses [3335].…”
Section: Discussionmentioning
confidence: 90%
“…So, the BMI values found in the TRAINED group and also the negative correlation found in our study between LOOH and the oxLDL levels reinforce the consistence of the favorable effects of the combined aerobic-resistance exercise training on the redox indexes. Moreover, we also found that in the TRAINED group, TAC levels were higher than in the SED group, which could buffer oxidative stress, thereby preventing the LDL oxidation [32]. Previous studies have also shown beneficial actions of exercise training protocols, including combined aerobic-resistance exercise training on the antioxidant defenses [3335].…”
Section: Discussionmentioning
confidence: 90%
“…Additionally, the VO 2 max level of the participants in this study was 48.20 ± 2.19 mL/kg/min which is above the 60th percentile for adult men in their 20s [ 33 ]. Bachi et al [ 34 ] suggested that the level of OS after exercise could be lower in people with higher VO 2 max and total antioxidant activity. However, considering that high-intensity acute exercise can be one of the main causes of increased OS in the body, it seems necessary to verify this in additional studies by analyzing serum ROS levels and/or antioxidant enzymes such as superoxide dismutase (SOD) and catalase, not only d-ROMs and BAP levels.…”
Section: Discussionmentioning
confidence: 99%
“…If samples were tested at multiple earlier timepoints after frequent exercise we may expect to see a rebound rise in anti-oxLDL antibodies, as has been reported in the literature ( 41 , 42 ). However, in a recent study by Bachi and colleagues, trained athletes after running a marathon exhibited no change in IgM or IgG anti-MDA-LDL antibodies immediately or 72-h after the race, despite increases in plasma oxLDL ( 27 ). Again, perhaps the timepoints tested missed any small dynamic changes with the utilised assay, or the elite fitness of the participants means that their baseline anti-oxLDL antibody levels are already fully induced.…”
Section: Discussionmentioning
confidence: 98%
“…Another possible explanation is that the highly optimised medical therapy renders the patients relatively non-ischaemic, and as such the biomarkers behave as though they were not sampled from patients with severe CAD. Indeed, there is no consensus in the literature on exercise-induced oxLDL changes in healthy participants (22)(23)(24)(25)(26)(27), and in some circumstances no changes in oxLDL levels, even following very high intensity exercise, have been found (28).…”
Section: Discussionmentioning
confidence: 99%